On conformal mapping of polygonal regions - Gutlyanskii, V. Ya.; Zaidan, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We develop Kufarev’s method for determining unknown parameters in the Schwarz-Christoffel integral in the case of conformal mapping of polygonal regions with boundary normalization.